Pengaruh Social Media Marketing dan Potongan Harga Terhadap Keputusan Pembelian Sepatu Merek Airwalk di Surabaya - Sugeng Purwanto; Muhammad Rafli (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research has the aim of explaining social media marketing and price discounts whether they have an influence on purchasing decisions using the research object of Airwalk brand shoes. The population used as the object of research is residents with Surabaya city ID cards and domiciled in Surabaya who have bought and used Airwalk brand shoes. While the sample in this study were 110 respondents. The results showed that social media marketing was able to contribute positively and significantly to purchasing decisions and price discounts were also able to contribute positively and significantly to purchasing decisions.